College Attendance System (CAS) in VB.NET and MSSQL: A Comprehensive Management Solution - Bashir, Adegoke Taiwo (Journal Dekstop Application (JDA), 2025)
The College Attendance System (CAS) is a desktop-based application developed to improve attendance management in tertiary institutions. Built with Visual Basic .NET and Microsoft SQL Server 2014, the system addresses the recurring problem of student absenteeism that contributes to academic underperformance in Nigerian higher education. CAS provides a structured digital platform that replaces error-prone manual methods with automated attendance tracking, real-time data access, and dynamic reporting features. Its architecture follows a three-tier model comprising presentation, business logic, and data access layers, ensuring modularity, maintainability, and scalability. The database is designed using a relational model that links schools, departments, courses, lecturers, and students, enabling efficient data management and reliable record retrieval. The system integrates multiple functionalities, including user authentication, attendance recording, data import and export, report generation, and audit logging, while prioritizing data security through encryption and parameterized queries. Results from implementation show that CAS significantly improves accuracy, reduces administrative workload, and increases institutional efficiency. A case study conducted in a Nigerian polytechnic revealed improvements in attendance rates—from 65% to 82%—and data accuracy—from 75% to 98%—while reducing administrative time by an average of 15 hours per week. Beyond its functional success, CAS serves as a valuable educational resource for students and developers by demonstrating practical application of database-driven software design. Although the system currently operates only on the Windows platform and lacks mobile or web integration, it provides a strong foundation for future development, including web-based expansion, biometric authentication, and advanced analytics. The project highlights the potential of open-source technologies to enhance institutional accountability and academic performance while fostering innovation in educational software development. The complete CAS package, including source code, database files, documentation, and demonstration materials, is freely available for academic use under specified licensing terms.